WAJAH PEMIKIRAN ISLAM INDONESIA - Mahfud (LP3M IAI Al-Qolam Malang, 2018)
Islam is religion in which all the values be based on God’s revelation that subsequently interacts with human culture. Rasionalism which focus on using of brain as tool to comprehend on God’s command being newcomer to effort comprehend of religion. Islamic rasionalize, progresive is unsaperated part from the religious history in Indonesia. Islamic thought in Indonesia was began in 1970s by Nurcholis Madjid. Others brainware as became pioneer from the appear of Indonesia Islamic thought is Abdurrahman Wahid in 1980s. Harun Nasution, Moeslim Abdurrahman are influential figure in Indonesia islamic thought context. Islamic thought which was pioneered by the several figure then was becoming as background from appeared ofislamic liberal as long as very controversial thought among muslim society. But the thougt becoming a part of dynamic Indonesia Islamic thougt as new pattern or new over in islamic world, Especially an over to observe islamic to be more rasional. Using of rasio in this idea was becoming a special characteristic, however using of brain was pointed to bring islamic from thought deterioration.